Analysis Of The Effect Of Compliance, Funding Decisions, And Foreign Ownership On Corporate Value Through Corporate Social Responsibility - Orlin Cicilia (Journal of Social Research, 2025)
corporate value becomes a reference for stakeholders and society towards a company, especially in seeing the compliance and concern of the company itself. This study aims to analyze the influence that occurs between compliance represented by good corporate governance, funding decisions, and foreign ownership on corporate value through corporate social responsibility. The sample companies that will be used in this research are companies classified as LQ 45 which are listed on the Indonesia Stock Exchange in 2017-2019. Hypothesis testing in this study uses multiple regression analysis involving moderated variables (moderated regression analysis) which not only involves the independent variable and the dependent variable, but also involves the moderating variable. The result of this research is funding decision (X2) has influence to corporate value (Y) and funding decision (X2) moderated by CSR (Z) has influence to corporate value (Y).